A retrospective study (2006–2020) of biopsy cases in pet guinea pigs (Cavia porcellus), degus (Octodon degus) and chinchillas (Chinchilla lanigera) at an exotic animal clinic in Tokyo, Japan - Minato Ueda; Takanori Shiga; Yasutsugu Miwa; Makoto Nakata; James K. Chambers; Kazuyuki Uchida; Nobuo Sasaki; Hiroyuki Nakayama (Journal of Comparative Pathology, 2026)

Regional variation in age-related decline of acetylcholine-induced sweating in the forearm and lower limb: an exploratory study in males - Tatsuro Amano; Tomoko Ichinose-Kuwahara; Hiroyuki Ueda; Narihiko Kondo; Yoshimitsu Inoue (Journal of Thermal Biology, 2025)

Japanese Planocerid Flatworms: Difference in Composition of Tetrodotoxin and Its Analogs and the Effects of Ingestion by Toxin-Bearing Fishes in the Ryukyu Islands, Japan - Hiroyuki Ueda; Masaaki Ito; Ryo Yonezawa; Kentaro Hayashi; Taiga Tomonou; Maho Kashitani; Hikaru Oyama; Kyoko Shirai; Rei Suo; Kazutoshi Yoshitake; Shigeharu Kinoshita; Shuichi Asakawa; et al. (Marine Biotechnology, 2024)
Tetrodotoxin (TTX), known as pufferfish toxin, is a potent neurotoxin blocking sodium channels in muscle and nerve tissues. TTX has been detected in various taxa other than pufferfish, including marine polyclad flatworms, suggesting that pufferfish toxin accumulates in fish bodies via food webs. The composition of TTX and its analogs in the flatworm Planocera multitentaculata was identical to those in wild grass puffer Takifugu alboplumbeus . Previously, Planocera sp. from Okinawa Island, Japan, were reported to possess high level of TTX, but no information was available on TTX analogs in this species. Here we identified TTX and analogs in the planocerid flatworm using high-resolution liquid chromatography–mass spectrometry, and compared the composition of TTX and analogs with those of another toxic and non-toxic planocerid species. We show that the composition of TTX and several analogs, such as 5,6,11-trideoxyTTX, dideoxyTTXs, deoxyTTXs, and 11-norTTX-6( S )-ol, of Planocera sp. was identical to those of toxic species, but not to its non-toxic counterpart. The difference in the toxin composition was reflected in the phylogenetic relationship based on the mitochondrial genome sequence. A toxification experiment using predatory fish and egg plates of P. multitentaculata demonstrated that the composition of TTX and analogs in wild T. alboplumbeus juveniles was reproduced in artificially toxified pufferfish. Additionally, feeding on the flatworm egg plates enhanced the signal intensities of all TTX compounds in Chelonodon patoca and that of deoxyTTXs in Yongeichthys criniger .

Terminal differentiation of keratinocytes was damaged in type 2 diabetic mice - Takeshi Takayanagi; Hiroyuki Hirai; Yohei Asada; Takaaki Yamada; Seiji Hasegawa; Eisuke Tomatsu; Yoshiteru Maeda; Yasumasa Yoshino; Izumi Hiratsuka; Sahoko Sekiguchi-Ueda; Megumi Shibata; Yusuke Seino; et al. (Molecular Biology Reports, 2022)

Effect of a proton-pump inhibitor on intestinal microbiota in patients taking low-dose aspirin - Hiroyuki Tsujimoto; Yuki Hirata; Yasuhiro Ueda; Naohiko Kinoshita; Hideki Tawa; Yasuyoshi Tanaka; Ryoji Koshiba; Kazuhiro Ota; Yuichi Kojima; Kazuki Kakimoto; Toshihisa Takeuchi; Takako Miyazaki; et al. (European Journal of Clinical Pharmacology, 2021)

Evidence for detection of rat P2X4 receptor expressed on cells by generating monoclonal antibodies recognizing the native structure - Tatsuhiro Igawa; Shuhei Kishikawa; Yoshito Abe; Tomohiro Yamashita; Saki Nagai; Mitsunori Shiroishi; Chinatsu Shinozaki; Hiroyuki Tanaka; Hidetoshi Tozaki-Saitoh; Makoto Tsuda; Kazuhide Inoue; Tadashi Ueda (Purinergic Signalling, 2019)

Maximum rate of sweat ions reabsorption during exercise with regional differences, sex, and exercise training - Tatsuro Amano; Megumi Hirose; Kana Konishi; Nicola Gerrett; Hiroyuki Ueda; Narihiko Kondo; Yoshimitsu Inoue (European Journal of Applied Physiology, 2017)

The concentration of iodine in horse serum and its relationship with thyroxin concentration by geological difference - Mariko Mochizuki; Noriyuki Hayakawa; Fumiko Minowa; Akihiro Saito; Katsumi Ishioka; Fukiko Ueda; Kimihiro Okubo; Hiroyuki Tazaki (Environmental Monitoring and Assessment, 2016)

Features and prognostic impact of distant metastasis in patients with stage IV lung adenocarcinoma harboring EGFR mutations: importance of bone metastasis - Daichi Fujimoto; Hiroyuki Ueda; Ryoko Shimizu; Ryoji Kato; Takehiro Otoshi; Takahisa Kawamura; Koji Tamai; Yumi Shibata; Takeshi Matsumoto; Kazuma Nagata; Kyoko Otsuka; Atsushi Nakagawa; et al. (Clinical & Experimental Metastasis, 2014)

Annual variation in biomass and the community structure of crustacean zooplankton over 5 years in Lake Toya, Japan - Syuhei Ban; Wataru Makino; Hiroyuki Sakano; Hiroyuki Haruna; Hiroshi Ueda (Limnology, 2013)

Chromosome elimination by wide hybridization between Triticeae or oat plant and pearl millet: pearl millet chromosome dynamics in hybrid embryo cells - Takayoshi Ishii; Toshie Ueda; Hiroyuki Tanaka; Hisashi Tsujimoto (Chromosome Research, 2010)

Observations of Coherent Turbulence Structures in the Near-Neutral Atmospheric Boundary Layer - Mitsuaki Horiguchi; Taiichi Hayashi; Hiroyuki Hashiguchi; Yoshiki Ito; Hiromasa Ueda (Boundary-Layer Meteorology, 2010)

Long-Term Declining Trends in River Water pH in Central Japan - Hiroki Matsubara; Shingo Morimoto; Hiroyuki Sase; Tsuyoshi Ohizumi; Hiroshi Sumida; Makoto Nakata; Hiromasa Ueda (Water, Air, & Soil Pollution, 2009)

Seasonal and Annual Fluxes of Inorganic Constituents in a Small Catchment of a Japanese Cedar Forest near the Sea of Japan - Masato Kamisako; Hiroyuki Sase; Taeko Matsui; Hiroko Suzuki; Akiomi Takahashi; Takuji Oida; Makoto Nakata; Tsumugu Totsuka; Hiromasa Ueda (Water, Air, & Soil Pollution, 2008)

Bacterial degradation of antibiotic residues in marine fish farm sediments of Uranouchi Bay and phylogenetic analysis of antibiotic-degrading bacteria using 16S rDNA sequences - Teruya MAKI; Hiroshi HASEGAWA; Hiroyuki KITAMI; Kyoko FUMOTO; Yukihiro MUNEKAGE; Kazumasa UEDA (Fisheries Science, 2006)

Nitrate Decrease with Isotopic Fractionation In Riverside Sediment Column During Infiltration Experiment - kouji Tsushima; Shingo Ueda; Hiroyuki Ohno; Norio Ogura; Takao Katase; Kunio Watanabe (Water, Air, & Soil Pollution, 2006)

Effects of G-CSF on left ventricular remodeling and heart failure after acute myocardial infarction - Hiroyuki Takano; Yingjie Qin; Hiroshi Hasegawa; Kazutaka Ueda; Yuriko Niitsuma; Masashi Ohtsuka; Issei Komuro (Journal of Molecular Medicine, 2006)

Regional differences in peripheral vasoconstriction of prepubertal boys - Yoshimitsu Inoue; Syunichi Nakamura; Kiichi Yonehiro; Tomoko Kuwahara; Hiroyuki Ueda; Tsutomu Araki (European Journal of Applied Physiology, 2006)

Effects of physical training on heat loss responses of young women to passive heating in relation to menstrual cycle - Tomoko Kuwahara; Yoshimitsu Inoue; Miyuki Taniguchi; Yukio Ogura; Hiroyuki Ueda; Narihiko Kondo (European Journal of Applied Physiology, 2005)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

Sex- and menstrual cycle-related differences in sweating and cutaneous blood flow in response to passive heat exposure - Yoshimitsu Inoue; Yoshiko Tanaka; Kaori Omori; Tomoko Kuwahara; Yukio Ogura; Hiroyuki Ueda (European Journal of Applied Physiology, 2005)

Estimation of nitrogen stable isotope turnover rate of Oncorhynchus nerka - Hiroyuki Sakano; Eiji Fujiwara; Seiichi Nohara; Hiroshi Ueda (Environmental Biology of Fishes, 2005)

Glutathione S-Transferase GSTM1, GSTT1 and p53 Codon 72 Polymorphisms in Human Tumor Cells - Masatsugu UEDA; Yao-Ching HUNG; Yoshito TERM; Koji KANDA; Mikio TAKEHARA; Hikari YAMASHITA; Hiroyuki YAMAGUCHI; Daisuke AKISE; Masayuki YASUDA; Koji NISHIYAMA; Minoru UEKI (Human Cell, 2003)

Importance of renal mitochondria in the reduction of TEMPOL, a nitroxide radical - Atsushi Ueda; Sohji Nagase; Hidekatsu Yokoyama; Mika Tada; Hiroyuki Noda; Horoaki Ohya; Hitoshi Kamada; Aki Hirayama; Akio Koyama (Molecular and Cellular Biochemistry, 2003)

Chemical modification of lipases with various hydrophobic groups improves their enantioselectivity in hydrolytic reactions - Shin-ichi Ueji; Ai Ueda; Hiroyuki Tanaka; Keiichi Watanabe; Takashi Okamoto; Yasuhito Ebara (Biotechnology Letters, 2003)

Erratum to: Development of new insulinomimetic zinc(II) picolinate complexes with a Zn(N2O2) coordination mode: structure characterization, in vitro, and in vivo studies - Yutaka Yoshikawa; Eriko Ueda; Kenji Kawabe; Hiroyuki Miyake; Toshikazu Takino; Hiromu Sakurai; Yoshitane Kojima (JBIC Journal of Biological Inorganic Chemistry, 2002)

Development of new insulinomimetic zinc(II) picolinate complexes with a Zn(N2O2) coordination mode: structure characterization, in vitro, and in vivo studies - Yutaka Yoshikawa; Eriko Ueda; Kenji Kawabe; Hiroyuki Miyake; Toshikazu Takino; Hiromu Sakurai; Yoshitane Kojima (JBIC Journal of Biological Inorganic Chemistry, 2002)

Gene delivery for genetically engineered mucosal cells with enhanced function - Naoki Nagatani; Masashige Shinkai; Yayoi Nagase; Hiroyuki Honda; Ken-ichiro Hata; Hirokazu Mizuno; Minoru Ueda; Takeshi Kobayashi (Biotechnology Letters, 2000)

Mechanisms underlying the age-related decrement in the human sweating response - Yoshimitsu Inoue; Manabu Shibasaki; Hiroyuki Ueda; Hiromichi Ishizashi (European Journal of Applied Physiology, 1999)

Immunochemically distinct NADP-linked isocitrate dehydrogenase isozymes in mitochondria and peroxisomes of Candida tropicalis - Toshiya Imajo; Hiroyuki Kawachi; Haruyuki Atomi; Shin-ichi Sanuki; Setsuko Yamamoto; Mitsuyoshi Ueda; A. Tanaka (Archives of Microbiology, 1997)

Ag-NOR variation in chromosomes of Chinese bitterlings,Rhodeus lighti andTanakia himantegus (Cypriniformes, Cyprinidae) - Takayoshi Ueda; Nobutaka Mashiko; Hiroyuki Takizawa; Yutaka Akai; Toshihiro Ishinabe; Ryoichi Arai; Hanling Wu (Ichthyological Research, 1997)

Characterization of the intron-containing citrate synthase gene from the alkanotrophic yeast Candida tropicalis : cloning and expression in Saccharomyces cerevisiae - Mitsuyoshi Ueda; Shin-ichi Sanuki; Hiroyuki Kawachi; Kaori Shimizu; Haruyuki Atomi; Atsuo Tanaka (Archives of Microbiology, 1997)